Screening and management of bladder and bowel dysfunction in general pediatric outpatient clinic: a prospective observational study - Achra Sumboonnanonda (2022)
Background: Bladder and bowel dysfunction (BBD) is a common disorder in children that is often associated with psychosocial and behavioral problems. Data specific to BBD in Asian children are comparatively scarce. Accordingly, this study aimed to investigate the prevalence of BBD and the response to standard urotherapy among Thai children attending the general pediatric outpatient clinic of Siriraj Hospital – Thailand’s largest national tertiary referral center. Methods: Children aged 4–12 years were recruited to complete the Dysfunctional Voiding Symptom Score (DVSS) questionnaire to screen for BBD during 2018 to 2020. Standard urotherapy, which consists of education and behavior management, was prescribed to those with a DVSS score that suggests the presence of BBD. Enrolled children and their caregivers were followed-up at 3 and 6 months. The Strengths and Difficulties Questionnaire (SDQ) was completed at baseline. DVSS scores at baseline, and at 3 months and 6 months after standard urotherapy were compared using repeated measures analysis of variance (ANOVA). Results: A total of 1,042 children completed the DVSS during the study period, and 90 (8.6%) were deemed to have BBD. The mean age of BBD children was 6.9 ± 2.2 years, and the female to male ratio was 2.9:1. The most common symptoms were defecation frequency (80.0%), difficult defecation (80.0%), curtsying (74.4%), urgency (68.9%), infrequent voiding (43.3%), and daytime incontinence (32.2%). Forty-one BBD children completed the SDQ, and 32.5% had scores suggestive of hyperactivity problems. Among the 24 BBD patients who were followed-up after 3 and 6 months of standard urotherapy, there was a significant improvement in DVSS results (9.5 ± 3.1 at baseline vs. 6.9 ± 3.4 at 3 months vs. 4.4 ± 3.9 at 6 months; p < 0.01). Nine of 12 patients with urinary incontinence showed complete response at 6 months. The overall Bristol stool score significantly improved from 2.6 ± 0.7 at baseline to 3.2 ± 1.0 at 6 months (p = 0.03). Conclusions: BBD is a prevalent condition among Thai children that is often associated with emotional and behavioral problems. Standard urotherapy prescribed in a general pediatric outpatient clinic setting yielded favorable outcomes in Thai children with BBD.